Bilis Bihis: A feasibility study on laundry business located in Mandaluyong City - Abadicio, Charles Darwin M.; Caneja, Madel C.; Francisco, Sophia Marie E.; Ramos, Justine Angel T.; Saldua, Bea Bianca D. 4 0 16; 5
u
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2